2019
DOI: 10.15537/smj.2019.1.23401
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an educational program on quality of life in patients undergoing hemodialysis in western Saudi Arabia

Abstract: Objectives: To assess health-related quality of life (QOL) among hemodialysis (HD) patients attending HD units in Jeddah, Saudi Arabia and to evaluate the effect of an educational program on health-related QOL. Method: One hundred HD patients were recruited and followed from 4 different dialysis units in Jeddah, Saudi Arabia between January 2018 and May 2018. The patients were divided into an intervention group (n=50) receiving educational program and control group (n=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
3
6
0
1
Order By: Relevance
“…Moreover, we found that those with higher education had better QOL than those with lower education in the domain of PCS. Several studies [34][35][36] have reported that the impact of having higher education is related to better QOL among CKD patients, particularly in the domain of PCS. This finding is consistent with a study conducted in the United States [37], which reported that higher and longer duration of education were associated with higher HRQOL scores.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that those with higher education had better QOL than those with lower education in the domain of PCS. Several studies [34][35][36] have reported that the impact of having higher education is related to better QOL among CKD patients, particularly in the domain of PCS. This finding is consistent with a study conducted in the United States [37], which reported that higher and longer duration of education were associated with higher HRQOL scores.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it can be observed that the overall performed safe laundry practices scores were satisfactory in both settings with no significant relations between overall staff laundry safe practices scores and pathogens (32,33,34) .…”
Section: Table (4): Subjects Distribution According To Laundry Procesmentioning
confidence: 82%
“…Berbagai pendekatan intervensi yang diidentifikasi dalam penelitian ini yaitu intervensi pendidikan untuk meningkatkan pengetahuan (Alikari et al, 2019;Bakarman et al, 2019;Başer & Mollaoğlu, 2019;Mina et al, 2019;Rafiee Vardanjani et al, 2016;Youssef Sharaf, 2016;, self regulation model (Howren et al, 2016), dukungan psikososial dan social support programme (Griva et al, 2018;Mansouri et al, 2020;Tao et al, 2020), penerapan motivational technique (Crown et al, 2017), self-care and selfmanagement berdasarkan konstruksi teori perilaku kognitif (Mahjubian et al, 2018;Zhianfar, Nadrian, Jafarabadi, et al, 2020).…”
Section: Intervensi Psikoedukasi Sacara Langsungunclassified